Bullying victimization and associated factors among school-aged adolescents in Africa: a systematic review and meta-analysis. - Gidey Rtbey; Fantahun Andualem; Girum Nakie; Setegn Fentahun; Mamaru Melkam; Getasew Kibralew; Gebresilassie Tadesse; Belete Birhan; Techilo Tinsae; Girmaw Medfu Takelle (PLoS ONE)
Background Bullying victimization during school age is a global public health concern. School-aged adolescents experiencing bullying victimization are more likely to encounter physical, cognitive, and mental health issues; including greater rates of depression, anxiety, and suicidal behaviors. This systematic review and meta-analysis was conducted to estimate the pooled prevalence of bullying victimization and its determinants among school-aged adolescents in Africa. Methods All studies reporting the prevalence of bullying victimization and its determinants among African school-aged adolescents were included based on the predefined eligibility criteria. We followed the Preferred Reporting Items for Systematic Review and Meta-Analysis(PRISMA), a guideline for reporting a systematic review and meta-analysis. A random-effects model was employed to estimate the pooled effect size of bullying victimization and its determinants with their odds ratio (OR) and a 95% confidence interval(CI). Funnel plots analysis and Egger's regression test were conducted to assess publication bias. Subgroup and sensitivity analyses were also performed. Results Twenty-five studies involving 41,716 school-aged adolescents were included in this systematic review and meta-analysis. The overall pooled prevalence of bullying victimization among school-aged adolescents in Africa was 46.35%, with a 95% CI (41.45, 51.24). According to the subgroup analysis of the study region, 49.17% of bullying victimization was reported in the Eastern region of Africa whereas, 32.73% was reported in the Southern region. Engaging in physical fights [OR=1.86; 95% CI: 1.66, 2.07], current substance use [OR=1.85; 95% CI: 1.31, 2.62], feeling lonely [OR=1.98; 95% CI: 1.49, 2.65], and being worried [OR=2.56; 95% CI: 2.12, 3.1] were significantly associated with bullying victimization. Conclusion and recommendation This review revealed that the pooled prevalence of bullying victimization among school-aged adolescents in Africa was high. To ensure adolescents' mental health and cultivate productive manpower, fostering a supportive environment in schools is mandatory.